A systematic review of fractional exhaled nitric oxide in the routine management of childhood asthma. Issue 3 (1st February 2016) - Gomersal, Tim; Harnan, Sue; Essat, Munira; Tappenden, Paul; Wong, Ruth; Lawson, Rod; Pavord, Ian; Everard, Mark Lloyd
Summary: Background: Fractional exhaled nitric oxide (FeNO) is a non‐invasive biomarker of eosinophilic inflammation which may be used to guide the management of asthma in childhood. Objectives: To synthesise the available evidence on the efficacy of FeNO‐guided management of childhood asthma. Methods: Databases including MEDLINE and the Cochrane Library were searched, and randomised controlled trials (RCTs) comparing FeNO‐guided management with any other monitoring strategy were included. Study quality was assessed using the Cochrane risk of bias tool for RCTs, and a number of outcomes were examined, including: exacerbations, medication use, quality of life, adverse events, and other markers of asthma control. Meta‐analyses were planned if multiple studies with suitable heterogeneity were available. However, due to wide variations in study characteristics, meta‐analysis was not possible. Results: Seven RCTs were identified. There was some evidence that FeNO‐guided monitoring results in improved asthma control during the first year of management, although few results attained statistical significance. The impact on severe exacerbations was unclear. Similarly, the impact on use of anti‐asthmatic drugs was unclear, and appears to depend on the step up/down protocols, and the clinical characteristics of patients. Conclusions: The potential benefit of FeNO monitoring is equivocal. Trends toward reduced exacerbation and increased medication use were seen, but typically failed to reach statistical significance. There are a number of issues that complicate data interpretation, including differences in the likely severity of included cohorts and variations in treatment algorithms. Further work is needed to systematically explore the impact of these parameters.Pediatr Pulmonol. 2016;51:316–328 . © 2016 Wiley Periodicals, Inc.